Physiological responses and time-motion characteristics of various small-sided soccer games in youth players - Hill-Haas, S. V.; Dawson, B. T.; Coutts, A. J.; Rowsell, G. J. (Journal of Sports Sciences, 2009)
The aim of this study was to examine acute physiological responses and time-motion characteristics associated with three different small-sided soccer game formats in youth players. Sixteen male soccer players aged 16.3 ± 0.6 years (mean ± s) completed three variations of a small-sided game (i.e. 2 vs. 2, 4 vs. 4, and 6 vs. 6 players) in which heart rate, rating of perceived exertion (RPE), blood lactate concentration, and time-motion characteristics were recorded. The pitch size was altered to keep the relative pitch area per player consistent for each game format. The 2 vs. 2 games exhibited greater blood lactate, heart rate, and RPE responses compared with 4 vs. 4 and 6 vs. 6 games (P < 0.05). The players travelled less (P < 0.05) distance at speeds of 0-7 km · h-1 in the 4 vs. 4 compared with the 2 vs. 2 games (1128 ± 10 m and 1176 ± 8 m, respectively). Average maximal sprint distances above 18 km · h-1 were lower (P < 0.05) in 2 vs. 2 than in 4 vs. 4 and 6 vs. 6 games (11.5 ± 3.9 m, 15.3 ± 5.5 m, and 19.4 ± 5.9 m, respectively), and in 4 vs. 4 compared with 6 vs. 6 games. The results show that as small-sided game formats decrease in size and relative pitch area remains constant, overall physiological and perceptual workload increases.